Angel and the badman [videorecording (DVD)] - Grant, James Edward, 1905-1966; Wayne, John, 1907-1979; Russell, Gail, 1924-1961; Carey, Harry, 1878-1947 (Front Row Entertainment, Inc., 2001)
Outlaw and gunslinger, Quirt Evans is wounded in a shootout and nursed back to health by a Quaker family. Complications arise when the Quaker daughter falls in love with the gunman and begins to reform him.